Histological and Molecular Characterization of Grape Early Ripening Bud Mutant - Da-Long Guo; Yi-He Yu; Fei-Fei Xi; Yan-Yan Shi; Guo-Hai Zhang (International Journal of Genomics)
An early ripening bud mutant was analyzed based on the histological, SSR, and methylation-sensitive amplified polymorphism (MSAP) analysis and a layer-specific approach was used to investigate the differentiation between the bud mutant and its parent. The results showed that the thickness of leaf spongy tissue of mutant (MT) is larger than that of wild type (WT) and the differences are significant. The mean size of cell layer L2 was increased in the mutant and the difference is significant. The genetic background of bud mutant revealed by SSR analysis is highly uniform to its parent; just the variations from VVS2 SSR marker were detected in MT. The total methylation ratio of MT is lower than that of the corresponding WT. The outside methylation ratio in MT is much less than that in WT; the average inner methylation ratio in MT is larger than that in WT. The early ripening bud mutant has certain proportion demethylation in cell layer L2. All the results suggested that cell layer L2 of the early ripening bud mutant has changed from the WT. This study provided the basis for a better understanding of the characteristic features of the early ripening bud mutant in grape.